THE IDIOMATIC MEANING OF 成语 CHENGYU WHICH HAS NATURAL ELEMENTS - Desy Veronica; Yulie Neila Chandra (Fakultas Sastra Universitas Darma Persada, 2020)
Mandarin is rich in vocabulary, including the form of 成语chéngyǔ, which is one of the most important parts in Mandarin. Every 成语chéngyǔ has its own background story, including history. Therefore, to understand the meaning of 成语chéngyǔ must understand the background of the story from 成语chéngyǔ. This article describes the idiomatic meaning of 成语chéngyǔ which has natural elements contained in the book of 成语故事Chéngyǔ Gùshi. Each Han character (汉字 Hànzì) that becomes an element in成语chéngyǔ does not reflect the overall meaning of the forming element, so that in general the成语chéngyǔ has idiomatic meaning. The method used in this writing is qualitative descriptive. There are 21成语chéngyǔ with natural elements in the book of 成语故事 Chéngyǔ Gùshi, however only one 成语chéngyǔ which contains partial idiom meanings, the other 20 of 成语chéngyǔ contains the full idiom meaning because of the forming elements do not reflect the idiomatic meaning. 成语chéngyǔ has a syntactic function in the sentence, as well as functions as advice, satire, and also praise to people indirectly.